Sulfide solid electrolyte, method for producing sulfide solid electrolyte, positive electrode for electricity storage device, and electricity storage device
By formulating a sulfide solid electrolyte with specific elemental ratios and a controlled crystal structure, the issue of low oxidation resistance in nitrogen-containing sulfide solid electrolytes is addressed, resulting in enhanced performance and efficiency in storage elements.
Patent Information
- Application Number
- JP2024182212
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-17
- Filing Date
- 2024-10-17
- Publication Date
- 2025-04-30
AI Technical Summary
Sulfide solid electrolytes containing nitrogen elements exhibit low oxidation resistance, which can lead to reduced performance and efficiency in storage elements.
A sulfide solid electrolyte with a specific crystal structure, containing lithium, sodium, or potassium, phosphorus, aluminum, nitrogen, and halogen elements, with carefully controlled molar ratios of (A/P) < 3.74 and (N/P) < 0.33, enhancing its oxidation resistance.
The sulfide solid electrolyte achieves high oxidation resistance, maintaining Coulomb efficiency and improving the performance of positive electrodes and storage elements.
Smart Images

Figure 2025069111000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a sulfide solid electrolyte, a method for producing a sulfide solid electrolyte, a positive electrode for an electricity storage element, and an electricity storage element. [Background technology]
[0002] Lithium ion secondary batteries are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The lithium ion secondary battery generally has a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and is configured to charge and discharge by transferring lithium ions between the electrodes. In addition, capacitors such as lithium ion capacitors are also widely used as storage elements other than lithium ion secondary batteries.
[0003] In recent years, there have been proposed electricity storage elements that use a solid electrolyte, such as a sulfide solid electrolyte, as the nonaqueous electrolyte, instead of a nonaqueous electrolyte solution in which an electrolyte salt is dissolved in a liquid such as an organic solvent.
[0004] Patent Document 1 discloses a compound A having a crystal structure and containing, as constituent elements, one or more divalent elements A, one or more halogen elements X, and a nitrogen element, the divalent element A and the halogen element X being composed of these elements. 0.5 A sulfide solid electrolyte is described in which the hydration energy of X is greater than the hydration energy of LiI. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2020 / 045634 Summary of the Invention [Problem to be solved by the invention]
[0006] Patent Document 1 describes that the sulfide solid electrolyte contains a nitrogen element, which can suppress a hydration reaction having low reversibility. However, the present inventors have found that the sulfide solid electrolyte contains a nitrogen element, which can reduce oxidation resistance.
[0007] The present invention has been made in light of the above circumstances, and an object of the present invention is to provide a sulfide solid electrolyte having high oxidation resistance, a method for producing such a sulfide solid electrolyte, and a positive electrode for an energy storage element and an energy storage element using such a sulfide solid electrolyte. [Means for solving the problem]
[0008] A sulfide solid electrolyte according to one aspect of the present invention has a crystalline structure and contains at least one element A selected from the group consisting of lithium, sodium, and potassium, at least one element M selected from the group consisting of phosphorus, aluminum, and boron, a nitrogen element, and at least one halogen element, in which the molar ratio (A / P) of the content of the element A to the content of the phosphorus element is less than 3.74, and the molar ratio (N / P) of the content of the nitrogen element to the content of the phosphorus element is less than 0.33.
[0009] A method for producing a sulfide solid electrolyte according to another aspect of the present invention includes processing a composition containing at least one element A selected from the group consisting of lithium, sodium, and potassium, phosphorus, at least one element M selected from the group consisting of aluminum and boron, nitrogen, and at least one halogen element, wherein the molar ratio (A / P) of the content of the element A to the content of the phosphorus is less than 3.74, and the molar ratio (N / P) of the content of the nitrogen element to the content of the phosphorus is less than 0.33.
[0010] A sulfide solid electrolyte according to another aspect of the present invention is produced by a method for producing a sulfide solid electrolyte according to another aspect of the present invention.
[0011] A positive electrode for an energy storage device according to another aspect of the present invention contains the sulfide solid electrolyte according to the aspect of the present invention.
[0012] An electric storage element according to another aspect of the present invention contains the sulfide solid electrolyte according to the aspect of the present invention. Effect of the Invention
[0013] According to any one aspect of the present invention, it is possible to provide a sulfide solid electrolyte having high oxidation resistance, a method for producing such a sulfide solid electrolyte, and a positive electrode for an energy storage element and an energy storage element using such a sulfide solid electrolyte. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a schematic cross-sectional view of an all-solid-state battery which is one embodiment of the energy storage element of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an energy storage device formed by assembling a plurality of energy storage elements according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] First, an outline of the sulfide solid electrolyte disclosed in this specification, a method for producing the sulfide solid electrolyte, and a positive electrode for an energy storage element and an energy storage element using such a sulfide solid electrolyte will be described.
[0016] [1] A sulfide solid electrolyte according to one aspect of the present invention has a crystalline structure and contains at least one element A selected from the group consisting of lithium, sodium, and potassium, at least one element M selected from the group consisting of phosphorus, aluminum, and boron, a nitrogen element, and at least one halogen element, wherein a molar ratio (A / P) of the content of the element A to the content of the phosphorus element is less than 3.74, and a molar ratio (N / P) of the content of the nitrogen element to the content of the phosphorus element is less than 0.33.
[0017] The sulfide solid electrolyte described in [1] above has high oxidation resistance. That is, even when the sulfide solid electrolyte described in [1] above is used in, for example, a positive electrode, the coulombic efficiency of a storage element using the positive electrode is unlikely to decrease. The reason why such an effect occurs is unclear, but the following reason is presumed. The sulfide solid electrolyte described in [1] above contains a nitrogen element and at least one element M selected from the group consisting of aluminum elements and the like. Therefore, in the sulfide solid electrolyte described in [1] above, it is considered that a structure with high oxidation resistance is formed due to the presence of the nitrogen element and the element M. Such a structure is, for example, a coating (protective layer) with high oxidation resistance containing the nitrogen element and the element M at the grain boundary or the like. In addition, it is considered that such a structure is difficult to maintain when the content of at least one element A selected from the group consisting of lithium element, sodium element, and potassium element or the nitrogen element is excessive. That is, it is presumed that the oxidation resistance of the sulfide solid electrolyte is enhanced when it contains nitrogen element and element M and the molar ratio (A / P) of the content of element A to the content of phosphorus element and the molar ratio (N / P) of the content of nitrogen element to the content of phosphorus element are within the above-mentioned ranges.
[0018] The presence of a crystalline structure can be confirmed by powder X-ray diffraction measurement. That is, in the present invention, "having a crystalline structure" means that a peak derived from the crystalline structure of the solid electrolyte is observed in the X-ray diffraction diagram in the powder X-ray diffraction measurement. The sulfide solid electrolyte described in [1] above may contain an amorphous part. Powder X-ray diffraction measurement is performed according to the following procedure. An airtight sample holder for X-ray diffraction measurement is filled with the sulfide solid electrolyte powder to be measured under an argon atmosphere with a dew point of -50°C or less. Powder X-ray diffraction measurement is performed using an X-ray diffractometer (MiniFlex II by Rigaku Co., Ltd.). The radiation source is CuKα radiation, the tube voltage is 30 kV, and the tube current is 15 mA, and the diffracted X-rays are passed through a 30 μm thick Kβ filter and detected by a high-speed one-dimensional detector (model number: D / teX Ultra 2). The sampling width is 0.01°, the scan speed is 5° / min, the divergence slit width is 0.625°, the receiving slit width is 13 mm (OPEN), and the scattering slit width is 8 mm.
[0019] In the present invention, the quantification of each element contained in the solid electrolyte is carried out by the following method. The sulfur element is quantified by the combustion-infrared absorption method. The nitrogen element is quantified by the inert gas fusion-thermal conductivity method. The halogen element is quantified by combustion ion chromatography. The lithium element, the sodium element, the potassium element, the phosphorus element, the aluminum element, the boron element, and the optional elements (elements other than the sulfur element, the nitrogen element, the halogen element, the lithium element, the sodium element, the potassium element, the phosphorus element, the aluminum element, and the boron element) are quantified by inductively coupled plasma atomic emission spectrometry (ICP-AES). However, among the optional elements, the hydrogen element and the oxygen element are quantified by the inert gas fusion-infrared absorption method. Among the optional elements, the carbon element is quantified by the combustion-infrared absorption method. In addition, in cases where it is impossible to measure each element using the above-mentioned methods, it can be measured using other methods that are considered to give equivalent measurement results.
[0020] [2] In the sulfide solid electrolyte described in [1] above, the element M may include an aluminum element.
[0021] [3] In the sulfide solid electrolyte according to the above [1] or [2], the halogen element may include a bromine element or an iodine element.
[0022] [4] The sulfide solid electrolyte according to any one of the above [1] to [3] may be represented by the following formula (1): A a PM b S c N d X e Y f (1) In the above formula (1), A is at least one selected from the group consisting of Li, Na, and K. M is at least one selected from the group consisting of Al and B. X is at least one selected from the group consisting of F, Cl, Br, and I. Y is at least one element other than A, P, S, M, N, and X. a, b, c, d, e, and f satisfy 2≦a<3.74, 0.01≦b≦1, 2≦c≦6, 0.01≦d<0.33, 0.01≦e≦1, and 0≦f≦1, respectively.
[0023] Each of the sulfide solid electrolytes described in the above [2] to [4] is a preferred embodiment of the present invention, has higher oxidation resistance, and is useful as a sulfide solid electrolyte.
[0024] [5] A method for producing a sulfide solid electrolyte according to another aspect of the present invention includes processing a composition containing at least one element A selected from the group consisting of lithium, sodium, and potassium, phosphorus, at least one element M selected from the group consisting of aluminum and boron, nitrogen, and at least one halogen element, wherein a molar ratio (A / P) of the content of the element A to the content of the phosphorus is less than 3.74, and a molar ratio (N / P) of the content of the nitrogen element to the content of the phosphorus is less than 0.33.
[0025] According to the method for producing a sulfide solid electrolyte described in the above item [5], a sulfide solid electrolyte having high oxidation resistance can be produced.
[0026] The term "composition" refers to a mixture of two or more compounds or simple substances (hereinafter, compounds and simple substances are collectively referred to as compounds, etc.). The entire composition, i.e., any compound, etc. contained in the composition may contain element A, phosphorus, element M, nitrogen, and halogen. The composition may also contain a compound, etc. that does not contain element A, phosphorus, element M, nitrogen, or halogen.
[0027] [6] In the method for producing a sulfide solid electrolyte according to the above [5], α M β N (wherein A is the above element A, M is the above element M, and α and β are values that give a stoichiometric ratio depending on the type of element M).
[0028] In the method for producing a sulfide solid electrolyte according to the above [6], the composition is A α M β Since the composition contains a compound represented by N, it is possible to suppress the release of nitrogen element from the composition during the production of the sulfide solid electrolyte. Therefore, it is possible to control the content of the nitrogen element in the composition with high accuracy. That is, since the composition contains the compound, it is possible to easily control the content of the nitrogen element relative to the content of the phosphorus element so as to be within the above range, so that a sulfide solid electrolyte having high oxidizing properties can be reliably and easily produced.
[0029] [7] A sulfide solid electrolyte according to another aspect of the present invention may be produced by the method for producing a sulfide solid electrolyte according to the above [5] or [6].
[0030] The sulfide solid electrolyte described in [7] above has high oxidation resistance.
[0031] [8] A positive electrode for an energy storage device according to another aspect of the present invention contains the sulfide solid electrolyte according to any one of the above [1] to [4] and [7].
[0032] The positive electrode for an electric storage device according to the above [8] contains a sulfide solid electrolyte having high oxidation resistance, and therefore the performance of an electric storage device using the positive electrode for an electric storage device according to the above [8] can be improved.
[0033] [9] An electric storage device according to another aspect of the present invention contains the sulfide solid electrolyte according to any one of the above [1] to [4] and [7].
[0034] The energy storage element described in [9] above uses a sulfide solid electrolyte having high oxidation resistance, and therefore can exhibit good energy storage element performance.
[0035] Hereinafter, a sulfide solid electrolyte, a method for producing a sulfide solid electrolyte, a positive electrode for an electric storage element, an electric storage element, a method for producing an electric storage element, an electric storage device, and other embodiments according to one embodiment of the present invention will be described in detail. Note that the names of the components (components) used in each embodiment may differ from the names of the components (components) used in the background art. In addition, element names may be represented by element symbols.
[0036] <Sulfide solid electrolyte> The sulfide solid electrolyte according to one embodiment of the present invention has a crystal structure. The sulfide solid electrolyte has a specific elemental composition described below. The sulfide solid electrolyte has high oxidation resistance. The sulfide solid electrolyte usually has lithium ion conductivity, sodium ion conductivity, or potassium ion conductivity. The sulfide solid electrolyte preferably has lithium ion conductivity. The sulfide solid electrolyte may also exhibit high ion conductivity.
[0037] (Crystal structure) The sulfide solid electrolyte preferably contains a high ion conduction phase (HICP) as a crystal structure. HICP is a specific crystal structure having diffraction peaks at diffraction angles 2θ of 19.9°±0.5° and 29.3°±0.5° in an X-ray diffraction pattern using CuKα radiation. When the sulfide solid electrolyte has a diffraction peak derived from HICP, it can exhibit good ion conductivity.
[0038] The sulfide solid electrolyte according to one embodiment of the present invention may have a crystal structure other than HICP. Other crystal structures include LGPS type, argyrodite type, Li 7 P 3 S 11 , Thio-LISICON system, etc. The sulfide solid electrolyte may have an amorphous portion.
[0039] (composition) The sulfide solid electrolyte contains at least one element A selected from the group consisting of lithium, sodium, and potassium, at least one element M selected from the group consisting of phosphorus, aluminum, and boron, nitrogen, and at least one halogen element X. The sulfide solid electrolyte also contains sulfur as a constituent element. Each constituent element will be described below.
[0040] The element A is at least one selected from the group consisting of lithium, sodium and potassium. The element A preferably includes lithium, and more preferably is lithium.
[0041] The upper limit of the molar ratio (A / P) of the content of element A to the content of phosphorus element is less than 3.74, preferably 3.72, more preferably 3.70, and even more preferably 3.68. The lower limit of the molar ratio (A / P) is preferably 3.00, more preferably 3.20, even more preferably 3.40, and even more preferably 3.60. The molar ratio (A / P) may be in a range that combines any of the lower limits and any of the upper limits described above. By setting the molar ratio (A / P) in the above range, the oxidation resistance can be increased.
[0042] The element M is at least one selected from the group consisting of aluminum and boron. It is believed that the sulfide solid electrolyte forms a structure with high oxidation resistance by containing the element M together with the nitrogen element. The element M preferably contains an aluminum element, and more preferably is an aluminum element.
[0043] The lower limit of the molar ratio (M / P) of the content of element M to the content of element phosphorus is preferably 0.01, more preferably 0.02, and even more preferably 0.03. The upper limit of the molar ratio (M / P) is preferably 0.15, more preferably 0.10, and even more preferably 0.05. By setting the molar ratio (M / P) to the above upper limit or less, the ionic conductivity of the sulfide solid electrolyte can be increased. The molar ratio (M / P) may be in a range that combines any of the above lower limits and any of the above upper limits.
[0044] The upper limit of the molar ratio (N / P) of the nitrogen element content to the phosphorus element content is less than 0.33, preferably 0.30, more preferably 0.25, even more preferably 0.20, even more preferably 0.15, and particularly preferably 0.10. The lower limit of the molar ratio (N / P) is preferably 0.01, more preferably 0.02, even more preferably 0.04, and even more preferably 0.06. The molar ratio (N / P) may be in a range that combines any of the lower limits and any of the upper limits described above. By setting the molar ratio (N / P) in the above range, the oxidation resistance can be increased. In addition, the portion of the sulfide solid electrolyte that comes into contact with water becomes basic, which makes it easier to suppress the generation of hydrogen sulfide.
[0045] Examples of the halogen element X include a fluorine element, a chlorine element, a bromine element, an iodine element, etc. The halogen element X preferably contains a bromine element or an iodine element, more preferably contains both a bromine element and an iodine element, and further preferably contains a bromine element and an iodine element.
[0046] The lower limit of the molar ratio (X / P) of the content of the halogen element X to the content of the phosphorus element is preferably 5.20, more preferably 0.56, further preferably 0.60, and even more preferably 0.64. The upper limit of the molar ratio (X / P) is preferably 0.82, more preferably 0.78, further preferably 0.74, and even more preferably 0.70. The molar ratio (X / P) may be within a range that combines any of the above lower limits with any of the above upper limits.
[0047] The molar ratio ((Br+I) / X) of the total content of bromine and iodine to the total content of halogen element X is preferably 0.5 or more, more preferably 0.7 or more, and even more preferably 0.9 or more. The molar ratio ((Br+I) / X) may be substantially 1.0.
[0048] The lower limit of the molar ratio (Br / P) of the content of bromine element to the content of phosphorus element is preferably 0.32, more preferably 0.34, further preferably 0.36, and even more preferably 0.38. The upper limit of the molar ratio (Br / P) is preferably 0.48, more preferably 0.46, further preferably 0.44, and even more preferably 0.42. The molar ratio (Br / P) may be within a range that combines any of the above lower limits with any of the above upper limits.
[0049] The lower limit of the molar ratio (I / P) of the content of iodine element to the content of phosphorus element is preferably 0.20, more preferably 0.22, further preferably 0.24, and even more preferably 0.26. The upper limit of the molar ratio (I / P) is preferably 0.34, more preferably 0.32, further preferably 0.30, and even more preferably 0.28. The molar ratio (I / P) may be within a range that combines any of the above lower limits with any of the above upper limits.
[0050] The lower limit of the molar ratio (S / P) of the sulfur element content to the phosphorus element content is preferably 3.20, more preferably 3.40, even more preferably 3.60, and even more preferably 3.80. The upper limit of the molar ratio (S / P) is preferably 4.80, more preferably 4.60, even more preferably 4.40, and even more preferably 4.20. The molar ratio (S / P) may be within a range that combines any of the above lower limits with any of the above upper limits.
[0051] The sulfide solid electrolyte according to one embodiment of the present invention may further contain an element Y other than the element A, phosphorus, element M, nitrogen, halogen element X, and sulfur. Examples of the other element Y include oxygen. However, the molar ratio (Y / P) of the content of the other element Y to the content of the phosphorus element in the sulfide solid electrolyte may be, for example, preferably 0 or more and 1 or less, more preferably 0.1 or less, and even more preferably 0.01 or less.
[0052] The composition of the sulfide solid electrolyte according to one embodiment of the present invention is preferably a combination of lithium, phosphorus, M, nitrogen, bromine, and sulfur as the halogen element X, a combination of lithium, phosphorus, M, nitrogen, iodine, and sulfur as the halogen element X, and a combination of lithium, phosphorus, M, nitrogen, bromine, iodine, and sulfur as the halogen element X. Among these, a combination of lithium, phosphorus, M, nitrogen, bromine, iodine, and sulfur as the halogen element X, and sulfur as the halogen element X is more preferable. In addition to the above combination of elements, the sulfide solid electrolyte may contain the other element Y as an optional element. In the sulfide solid electrolyte having the above combination of elements, the preferred content of each element is the same as described above.
[0053] The sulfide solid electrolyte according to one embodiment of the present invention is preferably represented by the following formula (1). A a PM b S c N d X e Y f (1) In the above formula (1), A is at least one selected from the group consisting of Li, Na, and K. M is at least one selected from the group consisting of Al and B. X is at least one selected from the group consisting of F, Cl, Br, and I. Y is at least one element other than A, P, S, M, N, and X. a, b, c, d, e, and f satisfy 2≦a<3.74, 0.01≦b≦1, 2≦c≦6, 0.01≦d<0.33, 0.01≦e≦1, and 0≦f≦1, respectively.
[0054] When the sulfide solid electrolyte according to one embodiment of the present invention has a composition represented by the above formula (1), the oxidation resistance is further improved. In the above formula (1), A preferably contains Li, and more preferably is Li. M preferably contains Al, and more preferably is Al. X preferably contains Br and I, and more preferably is Br and I. The preferred ranges of a, b, c, d, e, and f are the same as the preferred ranges of the molar ratios of the contents of each element relative to the content of phosphorus element described above. That is, the preferred range of a is the same as the preferred range of the molar ratio (A / P) described above, the preferred range of b is the same as the preferred range of the molar ratio (M / P) described above, the preferred range of c is the same as the preferred range of the molar ratio (S / P) described above, the preferred range of d is the same as the preferred range of the molar ratio (N / P) described above, the preferred range of e is the same as the preferred range of the molar ratio (X / P) described above, and the preferred range of f is the same as the preferred range of the molar ratio (Y / P) described above.
[0055] (Physical properties, uses, etc.) The lower limit of the ionic conductivity of the sulfide solid electrolyte according to one embodiment of the present invention at 25° C. is preferably 1 mS / cm, more preferably 2 mS / cm, even more preferably 3 mS / cm, even more preferably 4 mS / cm, and particularly preferably 5 mS / cm or 6 mS / cm. When the ionic conductivity of the sulfide solid electrolyte at 25° C. is equal to or higher than the lower limit, the charge / discharge performance of the storage element including the sulfide solid electrolyte can be improved. The upper limit of the ionic conductivity is not particularly limited, but may be, for example, 20 mS / cm or 10 mS / cm.
[0056] The ionic conductivity of the sulfide solid electrolyte according to one embodiment of the present invention is determined by measuring the AC impedance by the following method. In an argon atmosphere with a dew point of -50°C or less, 120 mg of sample powder is put into a powder molding machine with an inner diameter of 10 mm, and then uniaxially pressurized at 50 MPa or less using a hydraulic press. After releasing the pressure, 120 mg of SUS316L powder is put into the upper surface of the sample as a current collector, and then uniaxially pressurized again at 50 MPa or less using a hydraulic press. Next, 120 mg of SUS316L powder is put into the lower surface of the sample as a current collector, and then uniaxially pressurized at 360 MPa for 5 minutes to obtain a pellet for measuring ionic conductivity. The pellet for measuring ionic conductivity is inserted into an HS cell manufactured by Hosen Co., Ltd., and AC impedance is measured at a predetermined temperature. The measurement conditions are an applied voltage amplitude of 20 mV, a frequency range of 1 MHz to 100 mHz, and a measurement temperature of 25°C.
[0057] The shape of the sulfide solid electrolyte according to one embodiment of the present invention is not particularly limited, and is usually granular, blocky, or the like. The sulfide solid electrolyte can be suitably used as an electrolyte for a storage element such as a lithium ion secondary battery, particularly a lithium ion storage element. In particular, the sulfide solid electrolyte can be particularly suitably used as an electrolyte for an all-solid-state battery. The sulfide solid electrolyte can be used for any of a positive electrode, a separator, a negative electrode, and the like in a storage element. As described above, the sulfide solid electrolyte has high oxidation resistance, and is therefore suitably used as a sulfide solid electrolyte for a positive electrode.
[0058] <Method of manufacturing sulfide solid electrolyte> The method for producing a sulfide solid electrolyte according to one embodiment of the present invention comprises treating a composition containing at least one element A selected from the group consisting of lithium, sodium and potassium, phosphorus, at least one element M selected from the group consisting of aluminum and boron, nitrogen and at least one halogen element X. The composition usually also contains sulfur. According to the method for producing a sulfide solid electrolyte, a sulfide solid electrolyte having high oxidation resistance can be produced. The sulfide solid electrolyte produced by the method for producing a sulfide solid electrolyte is the same as the sulfide solid electrolyte according to one embodiment of the present invention described above.
[0059] (composition) The composition used as a raw material in the method for producing a sulfide solid electrolyte according to one embodiment of the present invention usually contains element A, phosphorus, element M, nitrogen, and halogen element X, as well as element sulfur. The composition is usually a mixture of two or more compounds containing at least one element selected from element A, phosphorus, element M, nitrogen, halogen element X, and sulfur. Any compound contained in the composition (mixture) may contain element A, phosphorus, element M, nitrogen, halogen element X, and sulfur. Two or more elements selected from element A, phosphorus, element M, nitrogen, halogen element X, and sulfur may be contained in one compound. For example, Li, which will be described later, is an example of a compound containing lithium and sulfur as element A. 2 S, a compound containing phosphorus and sulfur, as described below, P 2 S 5 The composition may contain a compound that does not contain any of the element A, the phosphorus element, the element M, the nitrogen element, the halogen element X, and the sulfur element.
[0060] In the above composition, the molar ratio (A / P) of the content of element A to the content of phosphorus is less than 3.74. Also, the molar ratio (N / P) of the content of nitrogen element to the content of phosphorus is less than 0.33. The suitable contents of each element in the above composition are the same as the suitable contents of each element in the sulfide solid electrolyte according to one embodiment of the present invention described above.
[0061] Examples of compounds containing phosphorus include P 2 S 3 , P 2 S 5 , P 2 O 5 , P 3 N 5 Among these, P 2 S 3 and P 2 S 5 is preferred, and P 2 S 5 The phosphorus-containing compound may be used alone or in combination of two or more.
[0062] Examples of the compound containing a halogen element X include compounds of element A, sulfur, phosphorus, etc., and halogen element X. Compounds of element A and halogen element X are preferred, and compounds of lithium and halogen element X are more preferred. Examples of the compound of lithium and halogen element X include LiF, LiCl, LiBr, and LiI. Compounds containing a halogen element X may be used alone or in combination of two or more.
[0063] As the compound containing a nitrogen element, a compound containing a nitrogen element and an element M is preferable. α M β Compounds represented by N (where A is the above element A, M is the above element M, and α and β are values that give a stoichiometric ratio depending on the type of element M) are more preferred. α M βThe compound represented by N can suppress the nitrogen element from being discharged from the composition in the treatment process described below. This is thought to be because, as described in Patent Document 1, for example, when a raw material compound containing nitrogen element and element M is used, the nitrogen defect generation energy is large, nitrogen defects are unlikely to be generated during the synthesis process, and nitrogen gas is unlikely to be generated. Therefore, it is possible to control the content of the nitrogen element in the composition with high precision. That is, when the composition is A α M β By including the compound represented by N, the molar ratio of the nitrogen element content to the phosphorus element content (N / P) can be easily controlled to be within the above range, so that a sulfide solid electrolyte with high oxidizing properties can be reliably and easily produced.
[0064] A α M β The compound represented by N includes a compound containing lithium, nitrogen and element M (hereinafter, also referred to as Li-MN-containing compound). The Li-MN-containing compound can be produced by the following procedure. First, Li 3 Nitrides of N and element M are prepared and mixed in a mortar or the like. Next, pellets of the mixed raw material compounds are produced. Next, the pellets are heat-treated to produce a Li-MN-containing compound. The means for preparing the Li-MN-containing compound is not limited to this, and it may be produced by other methods. For example, the raw material of the Li-MN-containing compound may be two or more compounds containing any of lithium element, element M, and nitrogen element. The Li-MN-containing compound may be produced by mechanical milling. The Li-MN-containing compound may be an industrially produced and commercially available one.
[0065] As the Li-MN-containing compound, a lithium composite nitride of element M is preferably used. As the lithium composite nitride of element M, for example, Li 1.5 Al 0.5 N, Li 1.5 B 0.5The lithium composite nitride may be, for example, a lithium composite nitride having a lithium element content relative to a nitrogen element content of, for example, Li 3 N and the like. For this reason, from the viewpoint of controlling the molar ratio (A / P) of the content of the A element to the content of the phosphorus element to be within the above range, it is preferable that the composition contains the lithium composite nitride. Furthermore, when the composition contains the lithium composite nitride, a sulfide solid electrolyte in which generation of hydrogen sulfide is suppressed can be produced. The reason for this is that when the composition contains the lithium composite nitride, the sulfide solid electrolyte obtained can reliably and easily contain a sufficient amount of nitrogen element, and becomes basic at the portion in contact with moisture, resulting in a state in which hydrogen sulfide is unlikely to be generated. Among the lithium composite nitrides, Li 1.5 Al 0.5 N is preferred.
[0066] Other compounds containing nitrogen include, for example, Li 3 N, P, P 3 N 5 , S 4 N 4 , S 2 N 2 , S 4 N 2 The nitrogen-containing compound may be used alone or in combination of two or more.
[0067] As the compound containing the element M, a compound containing a nitrogen element and the element M is preferable. α M β More preferred are compounds represented by N. Examples of other compounds containing element M include oxides of element M, sulfides of element M, nitrides of element M, and alloys of atoms of element M and lithium atoms. Examples of sulfides of element M include Al 2 S 3 Examples of the nitride of element M include AlN, BN, etc. The compound containing element M may be used alone or in combination of two or more.
[0068] Examples of compounds containing element A include halides of element A (such as the above-mentioned LiF, LiCl, LiBr, and LiI), α M β Compounds represented by N (Li 1.5 Al 0.5 N, etc.), Li 2 S., Li 2 O, Li 3 N, Li 2 CO 3 , metallic lithium, Na 2 S, Na 2 O, Na 3 N, Na 2 CO 3 , metallic sodium, K 2 S., K. 2 OK 3 N.K. 2 CO 3 , metallic potassium, etc. Among these, Li 2 S., Li 1.5 Al 0.5 Preferred are N, LiBr and LiI. The compound containing element A may be used alone or in combination of two or more.
[0069] Examples of compounds containing sulfur include Li 2 S, P 2 S 3 , P 2 S 5 , Al 2 S 3 Among these, Li 2 S, P 2 S 3 and P 2 S 5 is preferred, Li 2 S and P 2 S 5 The sulfur-containing compound may be used alone or in combination of two or more.
[0070] For example, in one embodiment, the composition comprises Li 2 S and P 2 S 5 and Li 1.5Al 0.5 The composition may include N, LiBr, and LiI, 2 S and P 2 S 5 and Li 1.5 Al 0.5 It may also be a composition consisting of N, LiBr and LiI.
[0071] (Processing) In the method for producing a sulfide solid electrolyte according to one embodiment of the present invention, the composition is treated to obtain a sulfide solid electrolyte. Examples of the treatment include a method of obtaining an intermediate by mechanical milling or the like and heating the intermediate. Note that the means for obtaining the intermediate is not limited to this, and a method other than mechanical milling, such as a melt quenching method, may also be used.
[0072] Mechanical milling may be either dry or wet, but wet is preferred because it can mix the raw material compounds more uniformly. Examples of mechanical milling include milling using a container-driven mill, a media-agitating mill, a high-speed rotary grinder, a roller mill, a jet mill, etc. Examples of container-driven mills include a rotary mill, a vibration mill, a planetary mill, etc. Examples of media-agitating mills include an attritor, a bead mill, etc. Examples of high-speed rotary grinders include a hammer mill, a pin mill, etc. Among these, a container-driven mill is preferred, and a planetary mill is particularly preferred.
[0073] The intermediate obtained by mechanical milling or the like may have a crystalline structure, but is preferably a so-called sulfide glass. "Sulfide glass" refers to a sulfide solid electrolyte containing an amorphous structure. When the intermediate is sulfide glass, Li 2 It is possible to obtain a sulfide solid electrolyte in which each element is highly dispersed and there is little low-stability crystalline phase such as S.
[0074] Heating (heat treatment) is performed on an intermediate obtained by mechanical milling or the like. As a result, a sulfide solid electrolyte in which at least a part of the intermediate is crystallized, preferably at least a part of which is crystallized into the above-mentioned HICP, is obtained. Heating (heat treatment) may be performed under a reduced pressure atmosphere or an inert gas atmosphere. The temperature range of the heating is, for example, preferably 150°C to 250°C, more preferably 170°C to 240°C, and even more preferably 180°C to 230°C. By setting the heating temperature to the above lower limit or higher, crystallization progresses sufficiently, and a sulfide solid electrolyte with sufficiently high oxidation resistance is obtained. In addition, by setting the heating temperature to the above upper limit or lower, precipitation of a phase with low ion conductivity (LICP: Low Ion Conduction Phase) is suppressed, and a sulfide solid electrolyte with high ion conductivity is obtained. LICP has a specific crystal structure that has diffraction peaks at diffraction angles 2θ in the ranges of 21.0°±0.5° and 28.0°±0.5° in an X-ray diffraction pattern using CuKα radiation.
[0075] <Positive electrodes for energy storage elements> A positive electrode for an electric storage device according to one embodiment of the present invention (hereinafter, also referred to as "positive electrode") contains the sulfide solid electrolyte according to one embodiment of the present invention. Since the positive electrode contains the sulfide solid electrolyte according to one embodiment of the present invention, which has high oxidation resistance, when used in an electric storage device, the charge / discharge efficiency of the electric storage device can be improved. The positive electrode includes a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer. The positive electrode may have an intermediate layer between the positive electrode substrate and the positive electrode active material layer.
[0076] The positive electrode may be used in combination with a solid electrolyte other than the sulfide solid electrolyte according to one embodiment of the present invention. Examples of the other solid electrolyte include a sulfide solid electrolyte other than the sulfide solid electrolyte according to one embodiment of the present invention, an oxide solid electrolyte, a dry polymer electrolyte, a gel polymer electrolyte, a pseudo-solid electrolyte, and the like, and the sulfide solid electrolyte is preferred.
[0077] As a sulfide solid electrolyte other than the sulfide solid electrolyte according to one embodiment of the present invention, for example, Li 2 SP 2 S 5 , Li 2 SP 2 S 5 - LiI, Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S 5 -LiBr, Li 2 SP 2 S 5 -Li 2 O, Li 2 SP 2 S 5 -Li 2 O-LiI, Li 2 SP 2 S 5 -Li 3 N, Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 - LiI, Li 2 S-SiS 2 -P 2 S 5 - LiI, Li 2 S.B. 2 S 3 , Li 2 SP 2 S 5 -Z m S 2n (where m and n are positive numbers, and Z is Ge, Zn, or Ga.) Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-SiS 2-Li x MO y (where x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga, or In.) Li 6 P.S. 5 Cl, Li 10 GeP 2 S 12 Among them, examples of sulfide solid electrolytes other than the sulfide solid electrolyte according to one embodiment of the present invention include Li 6 P.S. 5 An argyrodite-type solid electrolyte such as Cl can be suitably used.
[0078] The positive electrode substrate is conductive. Whether or not it has "conductivity" is determined by whether the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 -2 The threshold value is Ω·cm. The material of the positive electrode substrate is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferred from the viewpoints of potential resistance, high conductivity, and cost. The positive electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, etc., and a foil is preferred from the viewpoint of cost. Therefore, aluminum foil or an aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or an aluminum alloy include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H-4160 (2006).
[0079] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, even more preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, the strength of the positive electrode substrate can be increased while increasing the energy density per volume of the energy storage element. The "average thickness" refers to the average value of thicknesses measured at any five points (hereinafter the same applies to the average thickness).
[0080] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.
[0081] The positive electrode active material layer includes a positive electrode active material and a sulfide solid electrolyte. The positive electrode active material layer can be formed from a so-called positive electrode mixture including a positive electrode active material and a sulfide solid electrolyte. The positive electrode active material layer may contain a mixture or a composite including a positive electrode active material and a sulfide solid electrolyte. The positive electrode active material layer may contain optional components such as a conductive agent, a binder, a thickener, and a filler as necessary. One or more of these optional components may not be substantially contained in the positive electrode active material layer.
[0082] The positive electrode active material can be appropriately selected from known positive electrode active materials. As the positive electrode active material for a lithium ion secondary battery, a material capable of absorbing and releasing lithium ions is usually used. As the positive electrode active material, for example, α-NaFeO 2 Lithium transition metal composite oxides having a crystalline structure, lithium transition metal composite oxides having a spinel crystalline structure, polyanion compounds, chalcogen compounds, sulfur, etc. 2 As an example of a lithium transition metal composite oxide having a crystalline structure, Li[Li x Ni (1-x) ]O 2 (0≦x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O 2 (0≦x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Co (1-x) ]O 2 (0≦x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O 2 (0≦x<0.5, 0<γ<1, 0<1-x-γ), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O 2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1, 0<1-x-γ-β). Lithium transition metal composite oxides with spinel crystal structure include Li x Mn 2 O 4 , Li x Ni γ Mn (2-γ) O 4 Examples of polyanion compounds include LiFePO 4 , LiMnPO 4 , LiNiPO 4 , LiCoPO 4 , Li 3 V 2 (PO 4 ) 3 , Li 2 MnSiO 4 , Li 2 CoPO 4 Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, and molybdenum dioxide. The atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. These materials have a surface that is covered with other materials (e.g., LiNbO 3 In the positive electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.
[0083] The positive electrode active material is preferably a lithium transition metal composite oxide, more preferably a lithium transition metal composite oxide containing at least one of nickel, cobalt and manganese, even more preferably a lithium transition metal composite oxide containing at least two of nickel, cobalt and manganese, and even more preferably a lithium transition metal composite oxide containing nickel, cobalt and manganese. This lithium transition metal composite oxide is α-NaFeO 2It is preferable that the lithium transition metal composite oxide has a type crystal structure. By using such a lithium transition metal composite oxide, it is possible to increase the energy density.
[0084] The positive electrode active material is usually a particle (powder). The average particle size of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle size of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. In addition, when a composite of the positive electrode active material and another material is used, the average particle size of the composite is taken as the average particle size of the positive electrode active material. The "average particle size" means a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).
[0085] In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. During pulverization, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, an air classifier, etc. are used as necessary for both dry and wet methods.
[0086] The content of the positive electrode active material in the positive electrode active material layer is preferably 10% by mass to 95% by mass, more preferably 30% by mass to 90% by mass, and even more preferably 50% by mass to 85% by mass, with the lower limit being 60% by mass, and even more preferably 70% by mass. By setting the content of the positive electrode active material within the above range, it is possible to increase the discharge capacity of the energy storage element.
[0087] The content of all solid electrolytes in the positive electrode active material layer is preferably 5% by mass or more and 50% by mass or less, more preferably 10% by mass or more and 40% by mass or less, and even more preferably 15% by mass or more and 30% by mass or less. The content of the sulfide solid electrolyte according to one embodiment of the present invention relative to all solid electrolytes in the positive electrode active material layer is preferably 5% by mass or more and 100% by mass or less, more preferably 10% by mass or more and 100% by mass or less, and even more preferably 20% by mass or more and 100% by mass or less. By setting the content of the solid electrolyte within the above range, the discharge capacity of the storage element can be increased, etc.
[0088] Examples of the composite of the positive electrode active material and the solid electrolyte include a composite having a chemical or physical bond between the positive electrode active material and the solid electrolyte, a composite mechanically composited with the positive electrode active material and the solid electrolyte, etc. The composite may be one in which the positive electrode active material and the solid electrolyte are present in one particle, and examples of the composite include one in which the positive electrode active material and the solid electrolyte are in an aggregated state, one in which a coating containing the solid electrolyte is formed on at least a part of the surface of the positive electrode active material, etc.
[0089] A composite (composite particle) in which at least a part of the surface of a particle of a positive electrode active material is coated with a sulfide solid electrolyte according to one embodiment of the present invention is also a preferred embodiment of the present invention. Since at least a part of the surface of a particle of a positive electrode active material is coated with a sulfide solid electrolyte according to one embodiment of the present invention, good ion conductivity can be exhibited. In addition, the sulfide solid electrolyte according to one embodiment of the present invention has good oxidation resistance, and is therefore particularly useful as a solid electrolyte that coats a positive electrode active material. The content of the sulfide solid electrolyte in the composite is, for example, preferably 1% by mass or more and 20% by mass or less, more preferably 3% by mass or more and 10% by mass or less. The content of the composite in the positive electrode active material layer is, for example, preferably 60% by mass or more and 95% by mass or less, more preferably 70% by mass or more and 90% by mass or less, and even more preferably 75% by mass or more and 85% by mass or less.
[0090] The composite (composite particles) can be produced, for example, by a method of mixing a particulate or powdered positive electrode active material and a solid electrolyte while applying impact, compression, and shear force. At this time, components other than the positive electrode active material and the solid electrolyte may be further mixed to perform the composite. This composite treatment can be performed, for example, by a treatment using an apparatus equipped with an impeller (also called a rotating blade, impeller, etc.). Specifically, the above treatment is a treatment using a mechanical kneading method in which an impeller in a container is rotated to apply impact, compression, and shear force to the mixture of the positive electrode active material and the solid electrolyte between the impeller and the wall surface of the container. The above treatment may be performed in a dry or wet manner. The positive electrode active material and the solid electrolyte may be mixed in advance before performing the treatment using the apparatus equipped with the impeller. The positive electrode active material and the solid electrolyte may be separately charged into an apparatus equipped with an impeller.
[0091] The positive electrode active material layer may include the composite (composite particles), another solid electrolyte, a conductive agent, and a binder. In such a form, the solid electrolyte constituting the composite and the other solid electrolyte may both be the sulfide solid electrolyte according to one embodiment of the present invention. In addition, the other solid electrolyte may be a solid electrolyte other than the sulfide solid electrolyte according to one embodiment of the present invention. For example, the other solid electrolyte may be a sulfide solid electrolyte other than the sulfide solid electrolyte according to one embodiment of the present invention that is publicly known as exemplified above.
[0092] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbon materials, metals, conductive ceramics, and the like. Examples of carbon materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes, fullerenes, and the like. Examples of the shape of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. In addition, these materials may be used in a composite form. For example, a composite material of carbon black and carbon nanotubes may be used.
[0093] The content of the conductive agent in the positive electrode active material layer is preferably 0.5% by mass to 10% by mass, more preferably 1% by mass to 6% by mass, and the upper limit of the content of the conductive agent may be 5%, 4% by mass, or 3% by mass. By setting the content of the conductive agent in the above range, the energy density of the energy storage element can be increased.
[0094] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.
[0095] The content of the binder in the positive electrode active material layer is preferably 0.5% by mass to 10% by mass, more preferably 1% by mass to 6% by mass, and the upper limit of the binder content may be 5%, 4% by mass, or 3% by mass. By setting the binder content within the above range, the positive electrode active material can be stably maintained.
[0096] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be deactivated in advance by methylation or the like. In one embodiment of the present invention, the content of the thickener in the positive electrode active material layer may be 1% by mass or less, or 0.1% by mass or less, and the thickener may not be substantially contained.
[0097] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and their artificial products. In one embodiment of the present invention, the content of the filler in the positive electrode active material layer may be 1% by mass or less, 0.1% by mass or less, and may not substantially contain a filler.
[0098] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, solid electrolyte, conductive agent, binder, thickener, and filler.
[0099] The average thickness of the positive electrode active material layer is preferably 30 μm or more and 1,000 μm or less, more preferably 60 μm or more and 500 μm or less. By setting the average thickness of the positive electrode active material layer to the above lower limit or more, a storage element having a high energy density can be obtained. By setting the average thickness of the positive electrode active material layer to the above upper limit or less, the storage element can be made smaller.
[0100] <Electricity storage element> The electric storage element according to one embodiment of the present invention contains the sulfide solid electrolyte according to one embodiment of the present invention. As an electric storage element according to one embodiment of the present invention, an all-solid-state battery will be specifically described below. The electric storage element 10 in FIG. 1 is an all-solid-state battery, which is a secondary battery in which a positive electrode 1 and a negative electrode 2 are arranged with an isolating layer 3 interposed therebetween. The positive electrode 1 has a positive electrode substrate 4 and a positive electrode active material layer 5, and the positive electrode substrate 4 is the outermost layer of the positive electrode 1. The negative electrode 2 has a negative electrode substrate 7 and a negative electrode active material layer 6, and the negative electrode substrate 7 is the outermost layer of the negative electrode 2. In the electric storage element 10 shown in FIG. 1, the negative electrode active material layer 6, the isolating layer 3, the positive electrode active material layer 5, and the positive electrode substrate 4 are laminated in this order on the negative electrode substrate 7.
[0101] The energy storage element 10 contains a sulfide solid electrolyte according to one embodiment of the present invention in at least one of the positive electrode 1, the negative electrode 2, and the separator 3. More specifically, at least one of the positive electrode active material layer 5, the negative electrode active material layer 6, and the separator 3 contains a sulfide solid electrolyte according to one embodiment of the present invention. When the positive electrode 1 contains a sulfide solid electrolyte according to one embodiment of the present invention, the positive electrode 1 is a positive electrode for an energy storage element according to one embodiment of the present invention. Since the energy storage element 10 uses a sulfide solid electrolyte having high oxidation resistance, it is possible to improve the performance of the energy storage element, such as charge / discharge efficiency and capacity retention rate.
[0102] The energy storage element 10 may use a solid electrolyte other than the sulfide solid electrolyte according to one embodiment of the present invention. Examples of the other solid electrolyte include those exemplified in the description of the positive electrode for the energy storage element according to one embodiment of the present invention, and a sulfide solid electrolyte is preferable. In addition, a single layer in the energy storage element 10 may contain a plurality of different solid electrolytes, or each layer may contain a different solid electrolyte.
[0103] (positive electrode) The positive electrode 1 includes a positive electrode substrate 4 and a positive electrode active material layer 5 disposed directly or via an intermediate layer on the positive electrode substrate 4. In one embodiment of the present invention, the positive electrode 1 uses a positive electrode for an energy storage device according to one embodiment of the present invention.
[0104] (Negative electrode) The negative electrode 2 has a negative electrode substrate 7 and a negative electrode active material layer 6 disposed directly or via an intermediate layer on the negative electrode substrate 7. The configuration of the intermediate layer is not particularly limited and can be selected, for example, from the configurations exemplified for the positive electrode for an energy storage element according to one embodiment of the present invention.
[0105] The negative electrode substrate 7 is conductive. Metals such as copper, nickel, stainless steel, nickel-plated steel, and aluminum, or alloys thereof, carbonaceous materials, and the like are used as the material of the negative electrode substrate 7. Among these, copper or copper alloys are preferred. Examples of the negative electrode substrate 7 include foils, vapor deposition films, meshes, and porous materials, and foils are preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate 7. Examples of copper foil include rolled copper foil and electrolytic copper foil.
[0106] The average thickness of the negative electrode substrate 7 is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate 7 within the above range, the strength of the negative electrode substrate 7 can be increased, while the energy density per volume of the energy storage element 10 can be increased.
[0107] The negative electrode active material layer 6 includes a negative electrode active material. The negative electrode active material layer 6 can be formed from a so-called negative electrode mixture including a negative electrode active material. The negative electrode active material layer 6 may include a solid electrolyte, or may contain a mixture or a composite of a negative electrode active material and a solid electrolyte. The negative electrode active material layer 6 includes optional components such as a conductive agent, a binder, a thickener, and a filler as necessary. The types and suitable contents of these optional components in the negative electrode active material layer 6 are the same as those of each optional component in the positive electrode active material layer 5 described above. One or more of these optional components may not be substantially contained in the negative electrode active material layer 6.
[0108] The negative electrode active material layer 6 may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, solid electrolyte, conductive agent, binder, thickener, and filler.
[0109] The negative electrode active material can be appropriately selected from known negative electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the negative electrode active material for lithium ion secondary batteries. Examples of the negative electrode active material include metallic lithium; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li 4 Ti 5 O 12 , LiTiO 2、 TiNb 2 O 7 Examples of the materials include titanium-containing oxides such as titanium oxide, polyphosphate compounds, silicon carbide, and carbon materials such as graphite and non-graphitic carbon (easily graphitized carbon or non-graphitizable carbon). Among these materials, graphite and non-graphitic carbon are preferred. In the negative electrode active material layer 6, one of these materials may be used alone, or two or more of them may be used in combination.
[0110] "Graphite" refers to a material that has an average lattice spacing (d002 ) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. Artificial graphite is preferred from the viewpoint of availability of materials with stable physical properties.
[0111] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.
[0112] Here, the "discharged state" refers to a state in which the negative electrode active material, the carbon material, is discharged so that lithium ions that can be absorbed and released during charging and discharging are sufficiently released. For example, in a half cell using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metallic lithium as a counter electrode, the open circuit voltage is 0.7 V or more.
[0113] "Non-graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.
[0114] "Graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.
[0115] The negative electrode active material is usually a particle (powder). The average particle size of the negative electrode active material can be, for example, 1 nm or more and 100 μm or less. When the negative electrode active material is a carbon material, a titanium-containing oxide, or a polyphosphate compound, the average particle size may be 1 μm or more and 100 μm or less. When the negative electrode active material is Si, Sn, Si oxide, Sn oxide, or the like, the average particle size may be 1 nm or more and 1 μm or less. By setting the average particle size of the negative electrode active material to the above lower limit or more, the negative electrode active material can be easily manufactured or handled. By setting the average particle size of the negative electrode active material to the above upper limit or less, the electronic conductivity of the negative electrode active material layer 6 is improved. In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, or the like is used. The pulverizing method and the classifying method can be selected from, for example, the methods exemplified in the positive electrode for a storage element according to one embodiment of the present invention. When the negative electrode active material is a metal such as metallic lithium, the negative electrode active material layer 6 may be in the form of a foil.
[0116] The content of the negative electrode active material in the negative electrode active material layer 6 is preferably 10% by mass or more and 100% by mass or less, more preferably 30% by mass or more and 95% by mass or less, with the lower limit being 50% by mass, and even more preferably 70% by mass. When the negative electrode active material is a metal such as metallic lithium, the lower limit of the content of the negative electrode active material in the negative electrode active material layer 6 may be 95% by mass or may be 99% by mass. By setting the content of the negative electrode active material within the above range, it is possible to increase the discharge capacity of the energy storage element 10, etc.
[0117] When the negative electrode active material layer 6 contains a solid electrolyte, the content of the solid electrolyte is preferably 5% by mass or more and 90% by mass or less, more preferably 20% by mass or more and 70% by mass or less, and the upper limit may be even more preferably 50% by mass. By setting the content of the solid electrolyte within the above range, it is possible to increase the discharge capacity of the energy storage element 10, etc. When the sulfide solid electrolyte according to one embodiment of the present invention is used in the negative electrode active material layer 6, the content of the sulfide solid electrolyte according to one embodiment of the present invention relative to the total solid electrolyte in the negative electrode active material layer 6 is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 90% by mass or more, and even more preferably substantially 100% by mass.
[0118] The mixture or composite of the negative electrode active material and the solid electrolyte or the like may be the mixture or composite of the above-mentioned positive electrode active material and the solid electrolyte or the like, in which the positive electrode active material is replaced with a negative electrode active material.
[0119] The average thickness of the negative electrode active material layer 6 is preferably 30 μm or more and 1,000 μm or less, and more preferably 60 μm or more and 500 μm or less. By setting the average thickness of the negative electrode active material layer 6 to be equal to or more than the above lower limit, it is possible to obtain an energy storage element 10 having a high energy density. By setting the average thickness of the negative electrode active material layer 6 to be equal to or less than the above upper limit, it is possible to reduce the size of the energy storage element 10.
[0120] (isolation layer) The isolating layer 3 contains a solid electrolyte. Examples of the solid electrolyte include those exemplified in the description of the sulfide solid electrolyte according to one embodiment of the present invention and the positive electrode for a storage element according to one embodiment of the present invention. The content of the solid electrolyte in the isolating layer 3 is preferably 70% by mass or more, more preferably 90% by mass or more, even more preferably 99% by mass or more, and even more preferably substantially 100% by mass. When the sulfide solid electrolyte according to one embodiment of the present invention is used in the isolating layer 3, the content of the sulfide solid electrolyte according to one embodiment of the present invention relative to the total solid electrolyte in the isolating layer 3 is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 90% by mass or more, and even more preferably substantially 100% by mass.
[0121] The isolation layer 3 is Li 3 PO 4 The cathode may contain optional components such as a phosphate compound, an oxide, a halogen compound, a binder, a thickener, a filler, etc. The optional components such as a binder, a thickener, a filler, etc. may be selected from the materials exemplified in the positive electrode for an energy storage element according to one embodiment of the present invention.
[0122] The average thickness of the isolating layer 3 is preferably 1 μm or more and 50 μm or less, and more preferably 3 μm or more and 20 μm or less. By setting the average thickness of the isolating layer 3 to be equal to or more than the above lower limit, it is possible to reliably insulate the positive electrode 1 from the negative electrode 2. By setting the average thickness of the isolating layer 3 to be equal to or less than the above upper limit, it is possible to increase the energy density of the energy storage element 10.
[0123] <Electricity storage device> The energy storage element of the present embodiment can be mounted as an energy storage unit (battery module) formed by assembling a plurality of energy storage elements in a power source for an automobile such as an electric vehicle (EV), a hybrid vehicle (HEV), or a plug-in hybrid vehicle (PHEV), a power source for electronic devices such as a personal computer or a communication terminal, or a power storage power source, etc. In this case, it is sufficient that the technology of the present invention is applied to at least one energy storage element included in the energy storage unit.
[0124] 2 shows an example of an energy storage device 30 in which energy storage units 20, each of which is an assembly of two or more electrically connected energy storage elements 10, are further assembled. The energy storage device 30 may include a bus bar (not shown) that electrically connects the two or more energy storage elements 10, a bus bar (not shown) that electrically connects the two or more energy storage units 20, etc. The energy storage units 20 or the energy storage device 30 may include a status monitoring device (not shown) that monitors the status of the one or more energy storage elements 10.
[0125] <Method of manufacturing energy storage element> The method for producing an electric storage element according to an embodiment of the present invention can be carried out by a generally known method, except that the sulfide solid electrolyte according to an embodiment of the present invention is used as a part or the whole of the solid electrolyte. Specifically, the method for producing an electric storage element according to an embodiment of the present invention includes, for example, (1) preparing a positive electrode mixture, (2) preparing a material for an isolating layer, (3) preparing a negative electrode mixture, and (4) stacking a positive electrode, a isolating layer, and a negative electrode. Each step will be described in detail below.
[0126] (1) Positive electrode mixture preparation process In this step, a positive electrode mixture for forming a positive electrode (positive electrode active material layer) is usually prepared. The method for preparing the positive electrode mixture is not particularly limited and can be appropriately selected according to the purpose. For example, the positive electrode mixture can be prepared by mixing the positive electrode active material and the solid electrolyte using a mechanical milling method or the like. In addition, a mixture or composite of the positive electrode active material and the solid electrolyte can be prepared in advance by the above-mentioned method or the like, and the obtained mixture or composite can be mixed with other components.
[0127] (2) Preparation of materials for the isolation layer In this step, an isolation layer material for forming an isolation layer is usually prepared. When the energy storage element is an all-solid-state battery, the isolation layer material can be a solid electrolyte. The isolation layer material can be prepared by a conventional method. For example, a predetermined material can be processed by mechanical milling to obtain a solid electrolyte. The isolation layer material may be prepared by heating a predetermined material to a melting temperature or higher by a melt quenching method, melting and mixing the two at a predetermined ratio, and quenching the mixture. Other methods for synthesizing the isolation layer material include, for example, a solid phase method in which the material is sealed under reduced pressure and then fired, a liquid phase method such as dissolution deposition, a gas phase method, and firing under an argon atmosphere after mechanical milling.
[0128] (3) Negative electrode mixture preparation process In this process, a negative electrode mixture for forming a negative electrode (negative electrode active material layer) is usually prepared. The specific method for preparing the negative electrode mixture is the same as that for the positive electrode mixture. Instead of the negative electrode mixture, the negative electrode active material layer may be formed from lithium foil or the like.
[0129] (4)Lamination process In this step, for example, a positive electrode having a positive electrode substrate and a positive electrode active material layer, an isolation layer, and a negative electrode having a negative electrode substrate and a negative electrode active material layer are laminated. In this step, the positive electrode, isolation layer, and negative electrode may be formed in this order, or may be formed in the reverse order, and the order of formation of each layer is not particularly limited. The positive electrode is formed, for example, by pressure molding a positive electrode substrate and a positive electrode mixture, the isolation layer is formed by pressure molding an isolation layer material, and the negative electrode is formed by pressure molding a negative electrode substrate and a negative electrode mixture. The positive electrode, isolation layer, and negative electrode may be laminated by pressure molding a positive electrode substrate, a positive electrode mixture, an isolation layer material, a negative electrode mixture, and a negative electrode substrate at once. The positive electrode and the negative electrode may be molded in advance, respectively, and the isolation layer may be laminated by pressure molding. Each layer may be formed by coating or the like.
[0130] <Other embodiments> The sulfide solid electrolyte, the method for producing a sulfide solid electrolyte, the positive electrode for a storage element, and the storage element of the present invention are not limited to the above-mentioned embodiments, and various modifications may be made within the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and a part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, a part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.
[0131] For example, the electric storage element according to the present invention may include layers other than the positive electrode, the separator layer, and the negative electrode. The present invention can also be applied to an electric storage element including a bipolar electrode. The electric storage element according to the present invention may include a liquid. Examples of such an electric storage element include an electric storage element in which a nonaqueous electrolyte solution containing an ionic liquid or the like is filled into the gaps in the positive electrode active material layer 5, the separator layer 3, the negative electrode active material layer 6, and the like in the above-mentioned electric storage element 10. The electric storage element according to the present invention may be a capacitor or the like in addition to an electric storage element that is a secondary battery.
[0132] <Example> The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.
[0133] [Example 1] The following process will 3.67 PAl 0.03 S 3.95 N 0.06 Br 0.40 I 0.27 We synthesized a sulfide solid electrolyte represented by the following formula: Li 3 N and AlN were weighed out to a molar ratio of 1.2:1, mixed in a mortar, and pelletized. Then, the mixture was heat-treated at 750°C for 1 hour to obtain Li 1.5 Al 0.5 N was prepared. The Li 1.5 Al 0.5 X-ray diffraction analysis revealed that the main phase of N is Li 1.5 Al 0.5 It was confirmed that N. Li was placed in an argon atmosphere glove box with a dew point of -50°C or less. 2 S (99.98%, Aldrich), P 2 S 5 (99%, Aldrich), Li 1.5 Al 0.5 N, LiBr (99.999%, manufactured by Aldrich), and LiI (99.999%, manufactured by Aldrich) were weighed out to a molar ratio of 54.1:18.6:2.3:15.0:10.0, and then mixed in a mortar to prepare a composition containing element A (lithium), phosphorus, halogen elements (bromine and iodine), nitrogen, and element M (aluminum and sulfur). The above composition was placed in a sealed 80 mL zirconia pot containing 160 g of zirconia balls with a diameter of 4 mm. Mechanical milling was performed for 45 hours at a revolution speed of 510 rpm using a planetary ball mill (FRITSCH, model number Premium line PL-7) to obtain an intermediate. The intermediate was heated (heat-treated) at 220°C for 2 hours to obtain the sulfide solid electrolyte of Example 1. The heating temperature was set to be near the crystallization temperature and within ±50°C of the crystallization temperature. The crystallization temperature was determined by taking a part of the intermediate after the mechanical milling treatment and subjecting it to DSC measurement. The DSC measurement was performed under the following conditions. That is, a DSC device (Rigaku Thermo Plus DSC8230) was used, and a SUS sealed pan was used, and the temperature was increased from room temperature to 400°C at a rate of 10°C / min.
[0134] [Examples 2, 4, 5, Comparative Examples 1, 3 to 8] The sulfide solid electrolytes of Examples 2, 4, and 5 and Comparative Examples 1, 3 to 8 were obtained in the same manner as in Example 1, except that the amounts of raw material compounds used were adjusted so that the element ratios and composition formulas of the sulfide solid electrolytes were as shown in Table 1, and the heating temperature (HT) was set as shown in Table 1. Each heating temperature was within a range of ±50°C of the crystallization temperature determined in the same manner as in Example 1 above.
[0135] [Example 3] The following process will 3.67 PB 0.02 S 3.97 N 0.04 Br 0.40 I 0.27 We synthesized a sulfide solid electrolyte represented by the following formula: Li 3 N and BN were weighed out to a molar ratio of 1.1:1, mixed in a mortar, and pelletized. Then, the mixture was heat-treated at 800°C for 10 minutes to obtain Li 1.5 B 0.5 N was prepared. The Li 1.5 B 0.5 X-ray diffraction analysis revealed that the main phase of N is Li 1.5 B 0.5 It was confirmed that N. Li was placed in an argon atmosphere glove box with a dew point of -50°C or less. 2 S (99.98%, Aldrich), P 2 S 5 (99%, Aldrich), Li 1.5 B 0.5N, LiBr (99.999%, manufactured by Aldrich), and LiI (99.999%, manufactured by Aldrich) were weighed out to a molar ratio of 54.8:18.7:1.5:15.0:10.0, and then mixed in a mortar to prepare a composition containing element A, lithium, phosphorus, halogen elements bromine and iodine, nitrogen, and element M, boron, and sulfur. The above composition was placed in a sealed 80 mL zirconia pot containing 160 g of zirconia balls with a diameter of 4 mm. Mechanical milling was performed for 45 hours at a revolution speed of 510 rpm using a planetary ball mill (FRITSCH, model number Premium line PL-7) to obtain an intermediate. The intermediate was heated (heat-treated) at 180° C. for 2 hours to obtain a sulfide solid electrolyte of Example 3. The heating temperature was within a range of ±50° C. of the crystallization temperature determined in the same manner as in Example 1.
[0136] [Comparative Example 2] The following process will 3.67 PSi 0.01 S 3.97 N 0.04 Br 0.40 I 0.27 We synthesized a sulfide solid electrolyte represented by the following formula: Li 3 N and Si 3 N 4 The two were weighed out to a molar ratio of 5.1:1, mixed in a mortar, and pelletized. Then, the mixture was heat-treated at 800°C for 10 minutes to obtain Li 1.67 S 0.33 N was prepared. The Li 1.67 S 0.33 X-ray diffraction analysis revealed that the main phase of N is Li 1.67 S 0.33 It was confirmed that N. Li was placed in an argon atmosphere glove box with a dew point of -50°C or less. 2 S (99.98%, Aldrich), P 2 S 5 (99%, Aldrich), Li 1.67 S 0.33N, LiBr (99.999%, manufactured by Aldrich), and LiI (99.999%, manufactured by Aldrich) were weighed out to a molar ratio of 54.8:18.7:1.5:15.0:10.0, and then mixed in a mortar to prepare a composition containing element A, lithium element, phosphorus element, halogen elements bromine element and iodine element, nitrogen element, silicon element, and sulfur element. The above composition was placed in a sealed 80 mL zirconia pot containing 160 g of zirconia balls with a diameter of 4 mm. Mechanical milling was performed for 45 hours at a revolution speed of 510 rpm using a planetary ball mill (FRITSCH, model number Premium line PL-7) to obtain an intermediate. The intermediate was heated (heat treated) at 180° C. for 2 hours to obtain a sulfide solid electrolyte of Comparative Example 2. The heating temperature was within a range of ±50° C. of the crystallization temperature determined in the same manner as in Example 1.
[0137] [Confirmation of crystal structure] Using the above method, powder X-ray diffraction measurements were performed on each of the sulfide solid electrolytes of Examples 1 to 5 and Comparative Examples 1 to 8. The airtight sample holder for X-ray diffraction measurements was manufactured by Rigaku Co., Ltd. and sold under the trade name "General-purpose Atmosphere Separator." In the X-ray diffraction patterns of each of the sulfide solid electrolytes of the Examples and Comparative Examples, it was confirmed that they had diffraction peaks in the range of 2θ=19.9°±0.5° and 2θ=29.3°±0.5° due to HICP, and thus had a crystalline structure.
[0138] [Measurement of ionic conductivity] The ionic conductivity (σ 25 ) was determined by measuring the AC impedance using the Bio-Logic VMP-300 according to the above method. The measurement results are shown in Table 1.
[0139] [Measurement of hydrogen sulfide generation] For each of the sulfide solid electrolytes of Example 1 and Comparative Examples 4 and 5, hydrogen sulfide (H 2The amount of solid electrolyte generated was measured. A desiccator was placed in a dry box with a dry air atmosphere at a dew point of -35°C. Then, solid electrolyte powder (500 mg) was placed in a sealed desiccator (effective volume 2300 cm 3 The amount of hydrogen sulfide generated was measured using a hydrogen sulfide sensor (PGM-1860). The measurement results are shown in Table 1.
[0140] [Evaluation of oxidation resistance] The following measurement cells were prepared using each of the sulfide solid electrolytes of Examples 1 to 5 and Comparative Examples 1 to 8, and square wave voltammetry (SWV) measurements were performed to evaluate the oxidation resistance. In an argon atmosphere with a dew point of -50°C or less, 80 mg of sample powder (solid electrolyte to be measured) was put into a powder molder with an inner diameter of 10 mm, and then uniaxially pressed at 50 MPa or less using a hydraulic press. After releasing the pressure, graphite powder was put on the upper surface of the sample, and then uniaxially pressed at 360 MPa for 5 minutes using a hydraulic press again. Next, a metal foil made of a metal indium foil and a metal lithium foil attached thereto was placed on the lower surface of the sample, and then uniaxially pressed at 50 MPa or less to obtain a pellet-type measurement cell. This measurement cell was pressed in the stacking direction with a torque of 50 cNm using a pressing tool, and SWV measurements were performed under the following measurement conditions. (SWV measurement conditions) Voltage amplitude: 20mV Relaxation time: 50ms Step voltage: 1mV Voltage range: OCV to 4.5V Measurement temperature: 50℃ Measured peak current I MAX is shown in Table 1. Peak current I MAX When the value of the oxidation resistance is small, it can be determined that the oxidation resistance is improved.
[0141] [Fabrication of energy storage element] Using each of the sulfide solid electrolytes of Example 1 and Comparative Examples 4 and 5, an electricity storage element was produced in the following procedure. The positive electrode active material is LiNi 0.5 Co 0.2 Mn 0.3 O2 The surface of the LiNbO 3 The positive electrode active material was coated with a sulphide. The above positive electrode active material, each sulfide solid electrolyte, and fibrous carbon as a conductive agent were weighed out in a given mass ratio. Next, a binder (SBR) and butyl butyrate as a solvent were added to this mixture so that the solid content ratio was 60 mass%, and the mixture was kneaded in a hybrid mixer to form a positive electrode mixture. The obtained positive electrode mixture was applied to an aluminium foil (average thickness 20 μm) as a positive electrode substrate using a YBA type Baker applicator to form a positive electrode mixture with a basis weight of 15 mg cm. -2 More than 25mg cm -2 The coating was performed as follows. This was dried in an argon atmosphere dryer set at 100°C, at which the solvent volatilized, for 20 minutes under normal pressure, and then for 15 minutes under reduced pressure, to form a positive electrode active material layer on the positive electrode substrate. This was punched out into a circle with a diameter of 10 mm to prepare a positive electrode for evaluation. An all-solid-state battery was fabricated for each of the above-mentioned positive electrodes. 6 P.S. 5 80 mg of an argyrodite-type sulfide solid electrolyte represented by Cl was added, and pressure molding was performed by uniaxial pressing at room temperature at 100 MPa for several seconds to form an isolation layer. After releasing the pressure, the above-prepared positive electrode was added to one side of the isolation layer, and pressure molding was performed by uniaxial pressing at 160°C and 400 MPa for 5 minutes. After releasing the pressure, indium foil and lithium foil as negative electrodes, and SUS316L foil as negative electrode substrate were added to the side opposite to the bonding surface of the positive electrode, and bonding was performed by uniaxial pressing at room temperature at 50 MPa for several seconds. This was removed from the ceramic powder molding machine to obtain a storage element (all-solid-state battery).
[0142] [Charge / discharge test] A charge / discharge test was carried out on each of the obtained energy storage elements at 50°C in the following manner. Constant current / constant voltage charging was carried out at a current of 0.1C with a charge cut-off voltage of 3.75V. The charge was terminated until the current reached 0.025C. A rest period of 10 minutes was then provided. Then, constant current discharging was carried out at a current of 0.1C with a discharge cut-off voltage of 2.25V. The ratio of the discharge capacity to the initial charge capacity was calculated as the initial charge / discharge efficiency. Next, a charge / discharge cycle test was performed on each storage element at 50° C. in the following manner. Constant current / constant voltage charging was performed with a current of 0.2 C and a charge cut-off voltage of 3.75 V. The charge was terminated until the current reached 0.05 C. A rest period of 10 minutes was then provided. A constant current discharge was then performed with a current of 0.2 C and a discharge cut-off voltage of 2.25 V. A rest period of 10 minutes was then provided. This charge / discharge cycle was repeated 30 times. The ratio of the discharge capacity at the 30th cycle to the discharge capacity at the 1st cycle was determined as the capacity retention rate. Table 1 shows the results of the initial charge / discharge efficiency and the capacity retention rate.
[0143] [Table 1]
[0144] As shown in Table 1, the sulfide solid electrolytes of Comparative Examples 1, 2, 5, and 6, which do not contain nitrogen element or element M, Comparative Examples 3 and 4, which have a molar ratio (N / P) of the content of nitrogen element to the content of phosphorus element of 0.33 or more, and Comparative Examples 7 and 8, which have a molar ratio (A / P) of the content of lithium element (element A) to the content of phosphorus element of 3.74 or more, have a peak current I MAX was 11.2 or more, and the oxidation resistance was low. In contrast, the sulfide solid electrolytes of Examples 1 to 5, which contain nitrogen and element M, have a molar ratio (N / P) of the nitrogen element content to the phosphorus element content of less than 0.33, and a molar ratio (A / P) of the lithium element (element A) content to the phosphorus element content of less than 3.74, have a peak current I MAXThe oxidation resistance was high, with a value of less than 11.2. The energy storage element using the sulfide solid electrolyte of Example 1, which had high oxidation resistance, had higher initial charge / discharge efficiency and capacity retention rate than the energy storage elements using the sulfide solid electrolytes of Comparative Examples 4 and 5, which had low oxidation resistance. [Industrial Applicability]
[0145] The sulfide solid electrolyte according to the present invention is suitably used as a solid electrolyte for an electricity storage element such as an all-solid-state battery. [Explanation of symbols]
[0146] 1 positive electrode 2 negative electrode 3 isolation layer 4. Positive electrode substrate 5 Cathode active material layer 6 Negative electrode active material layer 7. Negative electrode substrate 10 Energy storage element (solid-state battery) 20 Energy Storage Unit 30 Energy storage device
Claims
1. It has a crystal structure, At least one element A selected from the group consisting of lithium, sodium, and potassium; Phosphorus element, At least one element M selected from the group consisting of aluminum and boron; Nitrogen element, At least one halogen element Contains the molar ratio (A / P) of the content of the element A to the content of the phosphorus element is less than 3.74; A sulfide solid electrolyte in which the molar ratio (N / P) of the nitrogen element content to the phosphorus element content is less than 0.
33.
2. The sulfide solid electrolyte according to claim 1 , wherein the element M includes an aluminum element.
3. The sulfide solid electrolyte according to claim 1 or 2, wherein the halogen element includes a bromine element or an iodine element.
4. The sulfide solid electrolyte according to claim 1 or 2, represented by the following formula (1): A a PM b S c N d X e Y f ・・・(1) In the above formula (1), A is at least one selected from the group consisting of Li, Na, and K. M is at least one selected from the group consisting of Al and B. X is at least one selected from the group consisting of F, Cl, Br, and I. Y is at least one element other than A, P, S, M, N, and X. a, b, c, d, e, and f respectively satisfy 2≦a<3.74, 0.01≦b≦1, 2≦c≦6, 0.01≦d<0.33, 0.01≦e≦1, and 0≦f≦1.
5. 1. A method for producing a sulfide solid electrolyte, comprising: treating a composition containing at least one element A selected from the group consisting of lithium, sodium, and potassium, phosphorus, at least one element M selected from the group consisting of aluminum and boron, a nitrogen element, and at least one halogen element, wherein a molar ratio (A / P) of a content of the element A to a content of the phosphorus element is less than 3.74, and a molar ratio (N / P) of the content of the nitrogen element to the content of the phosphorus element is less than 0.
33.
6. The composition is A α M β The method for producing a sulfide solid electrolyte according to claim 5, comprising the step of:
7. A sulfide solid electrolyte produced by the method for producing a sulfide solid electrolyte according to claim 5 or 6.
8. A positive electrode for an electric storage element, comprising the sulfide solid electrolyte according to claim 1 or 2.
9. An electric storage element comprising the sulfide solid electrolyte according to claim 1 or 2.
Citation Information
Patent Citations
Method for manufacturing sulfide solid electrolyte, sulfide solid electrolyte, all-solid battery, and method for selecting raw material compound used to manufacture sulfide solid electrolyte
WO2020045634A1